(untitled) (Revista Sistemas de Producción Agroecológicos, 2014)
In order to evaluate some of the egg of Japanese quail (Coturnix coturnix japonica) in early stance phase fed rations based on broken rice, rice flour, banana flour and cassava bran this work was performed in 450 eggs from an experiment of 250 quail 50 days old in a completely randomized experimental design with five treatments, five replicates of ten birds each. Diets with energy and protein levels are similar were used to meet the nutritional requirements. The treatments were based diets: corn and soybean meal (T1), brown rice flour 50% corn substituting (T2), 50% broken rice corn substituting (T3), substituting cassava bran 50% corn (T4 ) and banana flour replaces 50% corn (T5). The experimental phase lasted 24 weeks the water and diets were provided daily. The banana flour increased (P<0.05) the proportion of yolk, the other variables were not affected by the inclusion of alternative foods. The data showed no significant changes in egg characteristics. In conclusion diets of different treatments are an alternative power in maintaining the characteristics quail production most demanded by consumers.